1970
DOI: 10.1136/jcp.23.7.572
|View full text |Cite
|
Sign up to set email alerts
|

Thermal damage to red cells

Abstract: Heating whole blood in vitro to 50°C induces progressive morphological changes. Fractionation of whole blood and subsequent heating to 480C show the older cells to be less deformable.Morphological changes induced by heating were first observed over a century ago (Schultze, 1865) when microspherocytosis and fragmentation were noted. Similar gross changes were also noted after burning-injuries and reported by Shen,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

1972
1972
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 11 publications
1
10
0
Order By: Relevance
“…It has been suggested that it represents the distribution of susceptibilities of a population of cells to the damaging agent. Possibly this variation is one of age, comparable with the age variation which can be demonstrated in a population of red cells (Baar and Arrowsmith, 1970), the young cells being those which are easily inhibited and the oldest cells being the most resistant to damage. The greater sensitivity to damage by ultrasound of the processes involved in sulphate uptake is of particular interest and may be a more specific effect.…”
Section: Discussionmentioning
confidence: 58%
“…It has been suggested that it represents the distribution of susceptibilities of a population of cells to the damaging agent. Possibly this variation is one of age, comparable with the age variation which can be demonstrated in a population of red cells (Baar and Arrowsmith, 1970), the young cells being those which are easily inhibited and the oldest cells being the most resistant to damage. The greater sensitivity to damage by ultrasound of the processes involved in sulphate uptake is of particular interest and may be a more specific effect.…”
Section: Discussionmentioning
confidence: 58%
“…Echinocytosis, which is an indicator for morphological change is a characteristic of RBC thermal damage frequently used for this purpose. It was shown that one of the earliest morphological manifestations of RBC following heat injury is their transformation from disc to spherical shape [51].…”
Section: R T R T T K T R T Q R T (5)mentioning
confidence: 99%
“…Similar findings have been made in patients with burns (Arturson & Hjelm, 1966, 1969. Younger erythrocytes are more easily damaged by heat and burned patients have a cell population enriched in older erythrocytes (Baar & Arrowsmith, 1970 Arturson and M . Hjelm Baar, 1979).…”
Section: The Concentrations O J Hexosemonophosphates In Erythrocymentioning
confidence: 99%